Pengaruh Penempatan Kerja Terhadap Prestasi Kerja Karyawan Pada Hotel Batiqa Palembang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2024)
ABSTRACT This study aims to determine the effect of job placement on employee performance at the Batiqa Hotel Palembang. The method used is a quantitative method with a total sample of 73 employees. The data analysis technique used in this study is the classic assumption test, linear regression analysis, the coefficient of determination and hypothesis testing. Partial t-test results obtained a significance value of 0.000